Atlantic St. John's Wort, Hypericum tenuifolium Synonym: Hypericum reductum - Debbie Miller; Mack Thetford; Chris Verlinde; Gabriel Campbell (EDIS, 2018)
Atlantic St. John’s wort occurs throughout Florida and more broadly west to Alabama and northeast to North Carolina on beach dunes and scrub plant communities frequently associated with wet depression areas. Hypericum is a large genus of plants with 31 species in Florida alone (Wunderlin et al. 2017). This plant is a prolific flower producer that attracts numerous pollinators. https://edis.ifas.ufl.edu/sg170